A novel segmental cored column for upgrading the seismic performance of underground frame structures. Issue 131 (April 2020) - Lu, Dechun; Wu, Chunyu; Ma, Chao; Du, Xiuli; El Naggar, M. Hesham
Abstract: A novel segmental cored column (SCC) is proposed to enhance the seismic performance of underground frame structures, especially the interlaminar deformability of the intermediate columns. The basic composition and behaviour mechanism of the SCC are introduced. An analytical model for calculating the horizontal load-displacement curve and the interlaminar deformability of the SCC is established, and pushover simulations are conducted to verify its efficacy. The developed model is then employed to investigate the critical factors that may affect the interlaminar deformability envelope of the SCC. To further demonstrate the feasibility of the SCC in upgrading the seismic performance of underground frame structures, the seismic responses of the same structure are analysed considering alternative column design, i.e., conventional rectangular or circular columns, or the SCC. The obtained results demonstrate that the structure retrofitted with the SCC experiences less damage and exhibits better seismic performance compared to those designed with conventional rectangular or circular columns. Highlights: A novel SCC with excellent interlaminar deformability is designed. An analytical model about the F-Δ curves of SCC is proposed. The effect of axial load ratio is included in seismic performance evaluation index. The validity of SCC for upgrading seismic performance is verified in Daikai station.